Multiliteracies in English as an additional language classrooms : methods, approaches, and lessons - De Oliveira, Luciana C.; Menda, Ana Maria; Vicentini, Cristiane (Emerald Publishing Limited : Information Age Publishling, 2021)
"This book, entitled Multiliteracies in English as an Additional Language Classrooms: Methods, Approaches, and Lessons, presents different practices and strategies for the English as an additional language classroom as well as units that could be adapted to various grade levels, English language proficiency levels, and linguistic and cultural backgrounds. The research, lessons, and concepts included in the book present innovative ideas in EAL education. The chapters are the result of a professional learning program for 30 English as a Foreign Language (EFL) teachers from Brazil, held at the University of Miami's School of Education and Human Development in the Spring semester of 2018. The program, entitled "Six-Week English Language Certificate Program for High School English Teachers from Brazil (PDPI)," contained several components related to language development and methodology, including orality, reading, writing, linguistic and grammatical knowledge, and interculturality. The program was guided by the principle of multiliteracies, with a focus on English language development through new possibilities to participate in meaning making that incorporates verbal, visual, body language, gestures, and audiovisual resources"-- Provided by publisher.
Keywords: English language -- Study and teaching (Secondary) -- Foreign speakers.; English teachers -- Training of -- Brazil.; Education -- Teaching -- Subjects -- Language Arts.; Language teaching theory and methods.; Teaching of reading, writing and numeracy.; Educational: Language, literature and literacy.; elektronické knihy; electronic books